2018
DOI: 10.1590/s0004-2803.201800000-59
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cancer in Brazil: Mortality Trends and Projections Until 2029

Abstract: BACKGROUND: Pancreatic cancer is one of the main cancer-related causes of death in developed countries, and one of the most lethal malignant neoplasms. This type of cancer is classified as the ninth most frequent in the world. OBJECTIVE: Analyze temporal trends for pancreatic cancer in Brazil in the period 2000-2014 and calculate mortality projections for the period 2015-2029. METHODS: Ecological study, with temporal series, based on information provided by the Brazilian Mortality Information System. Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 28 publications
1
23
0
7
Order By: Relevance
“…The trends are assessed throughout time, according to significant modifications in their evolution patterns. Joinpoint regression has been applied to different fields, to evaluate changes in time series data, especially in health studies 15 …”
Section: Methodsmentioning
confidence: 99%
“…The trends are assessed throughout time, according to significant modifications in their evolution patterns. Joinpoint regression has been applied to different fields, to evaluate changes in time series data, especially in health studies 15 …”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, for men, a significant upward trend was observed from 2000 to 2004, with an annual percentage change of 3.7% (95% confidence interval: 0.6 to 7.0), followed by a period of stability, but increasing again from 2010 to 2014, with an annual percentage change of 2.7% (95% confidence interval: 0.2 to 5.2). 5 A comparison of incident rates for pancreatic cancer among 43 countries revealed that in Brazil, there were non-statistically significant annual percentage increases in age-adjusted incident rates for pancreatic cancer, of 2.4% for men, and 0.1 % for women from 1988 to 2007 (the most recent data available). For men, the increase in the rate was constant over the period of observation and it occurred at the same pace for all birth cohorts analyzed.…”
mentioning
confidence: 99%
“…In Brazil, pancreatic cancer currently ranks 13th place in incidence and 6th place in mortality 1 , representing 2% of all malignant tumors and being responsible for 4% of all cancer-related deaths 2 . The majority of these cases are concentrated in the Southeast region, particularly in the State of São Paulo 3 . Importantly, it has been shown that the incidence of pancreatic cancer in Brazil has almost doubled in the past two decades 4 , and recent projections foresee further increments in both incidence and mortality in the next 10 years 3 .…”
Section: Introductionmentioning
confidence: 99%